1998
DOI: 10.1086/515347
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ‐Induced Activation of Indoleamine 2,3‐Dioxygenase in Cord Blood Monocyte‐Derived Macrophages Inhibits the Growth of Group B Streptococci

Abstract: Neonatal sepsis is most often caused by group B streptococci (GBS) and is a major cause of death in the neonatal period. The response of the immune system in the newborn child has received much attention and is thought to be deficient in a number of ways. The effector response of neonatal monocyte-derived macrophages (MDM) was investigated. Interferon-gamma induced the activation of indoleamine 2,3-dioxygenase in MDM and inhibited the growth of GBS. Both effects were enhanced by the addition of tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 16 publications
5
73
2
3
Order By: Relevance
“…IDO activity has first been described as being induced by IFN treatment of monocytes, macrophages and other types of cells potentially endowed with phagocytic and antigen-presenting capacity [15][16][17]. In this context, it was hypothesized that IDO production by either depleting tryptophan or by the production of toxic metabolites would help hampering bacterial proliferation, ultimately boosting host's defenses [18].…”
Section: Discussionmentioning
confidence: 99%
“…IDO activity has first been described as being induced by IFN treatment of monocytes, macrophages and other types of cells potentially endowed with phagocytic and antigen-presenting capacity [15][16][17]. In this context, it was hypothesized that IDO production by either depleting tryptophan or by the production of toxic metabolites would help hampering bacterial proliferation, ultimately boosting host's defenses [18].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, nicotinamide has been shown to protect ␤-cells from certain toxins and the effects of nitric oxide (31). There is evidence for a role of tryptophan catabolism, by the induction of the specific enzyme IDO, in the immune response of neuronal inflammation due to disease or injury, as well as its involvement in malignancy (9,10), in vitro antimicrobial activity (11)(12)(13)(14), and in vitro inhibition of T-cell proliferation (8). More recently, tryptophan depletion has been linked to the maintenance of pregnancy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Localized depletion of tryptophan in vivo has also been implicated in the immune evasion of certain tumors (9,10). Indoleamine 2,3-dioxygenase (IDO), the enzyme that regulates the rate-limiting step involved in the catabolism of tryptophan to kyneurenine, is also involved in the control of microbial infections (11)(12)(13)(14) and has been shown to have antioxidant properties (15)(16)(17). Pregnancy maintenance has also been associated with tryptophan catabolism by preventing the proliferation of maternal T-cells in response to tissues of the fetus expressing HLA alleles of the father (18).…”
mentioning
confidence: 99%
“…Previous reports demonstrated that the depletion of trp by IDO in the intracellular pool or microenvironment mediated an antimicrobial activity (11). Similar logic was applied to explain the immunomodulatory effects induced by IDO (4,5,12,13).…”
Section: Inhibition Of Nf-b and Induction Of Apoptosis Is Specific Tomentioning
confidence: 92%